MATHEMATICAL COMMUNICATION AND CONNECTIONS STUDENTS’ ABILITY THROUGH PROBLEM-BASED LEARNING - Taufiqurrohman, Erik; Sabandar, Jozua; Tapilouw, Marthen ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
The problem in this research is still the low of communication ability and mathematics connection and the independence of student learning MTs. This study aims to determine and examine whether the achievement and improvement of communication skills and mathematical connections and student learning independence using a problem-based approach is better than the learning by using ordinary learning, knowing the association between communication skills with mathematical connections, mathematical communication with learning independence and ability mathematical connection with the independence of learning both groups of students. This research uses quasi experimental research method with non equivalent control group design and using purposive sampling technique. The population of the research were the students of class VIII in one of MTs in Subang. The sample used was the students of class VIII E as the experimental class and VIII G as the control class. The data collection from this research is in the form of test and non-test. Both groups were given pretest and postes the ability of mathematical communication and questionnaires to measure students' learning independence. The form of test used is a test of the ability of communication and mathematical connections while to measure student learning independence using non-test instruments. The results showed that: the achievement and improvement of communication skills and mathematical connections and learning independence of students who received learning by using a problem-based approach is better than students who received regular learning. There is a strong association between communication skills with mathematical connections, mathematical communication with learning independence and mathematical connection ability with learning independence.